Peculiarities of adaptation of educational tasks in Ukrainian language for pupils of secondary school age with speech disorders - Pavliuk, Roman; Datsenko, Iryna (Educological discourse, 2023)
The article is devoted to the problems of adapting educational materials in Ukrainian language for children of secondary school age with speech disorders. Adaptation of educational materials is quite an important task both for teacher's assistants and for the teacher himself, the child. Children with special educational needs often encounter various learning barriers on their way, to overcome which it is important for teachers working in the system of inclusive education to use various technologies, including the technology of differentiated teaching, thanks to which the teacher gets the opportunity to take into account the differences between children and ensure an optimal and effective educational process for each of them. Therefore, mastering the Ukrainian language at an appropriate level will serve the child's successful education and life. Children with special educational needs are quite vulnerable, and the correct adaptation of tasks and correct teaching of the Ukrainian language for such children can give a good result for further successful learning. The purpose of the article is to theoretically investigate the problem of adapting educational tasks and to propose methodological recommendations for adapting educational tasks in Ukrainian language for children of secondary school age with speech disorders. The following methods were used in our research: theoretical analysis of the problem of adaptation in order to reveal the peculiarities of adaptation of visual tasks from the Ukrainian language for children of secondary school age with speech disorders; empirical (expert evaluation of materials from the Ukrainian language, expert interviews) to find out the current state of teacher preparation for working with a child with a speech disorder; generalization and interpretation of research results. Based on the results of the research, we came to the conclusion that it is important for the teacher to understand that the main purpose of using adapted tasks in the educational process of an inclusive educational institution is to create the most comfortable conditions for the effective training of a person with special educational needs, ensuring that he/she achieves such a level of mastery of the material that corresponds his/her cognitive capabilities, abilities (but not below the minimum), as well as the development of these capabilities and abilities. We see the development of methodological recommendations for adapting Ukrainian language tasks for children with special educational needs as prospects for further research.